Do foreign investors trading behaviors affect mutual fund performances or vice versa? - Auzairy, Noor Azryani; Ibrahimy, Ahmad Ibn (International Journal of Asian Social Science, 2023)
This paper is to examine the trading behavior, buy and sell, by foreign investors: institutional and retail investors, on the performance of the mutual funds (information contribution effect). The impact of mutual funds performances on the trading behavior (feedback effect) of foreign investors are also to be investigated. Since there have been increasing demand for much more secured and cheaper investment, such as mutual funds, the study on these funds is crucial. Granger causality, Spearman’s rho and Vector Autoregressive model analyses are applied on daily data of foreign institutional and retail buy, sell and net flows volume and Malaysia’s average mutual fund returns from 1st October 2009 to 31st December 2019. The findings reveal that only foreign retail investors have cause-effect relationships with the performance of the mutual funds. Thus, mutual funds companies, especially in the emerging countries, should be given more attention to foreign retail investors in attracting them to remain invest in our mutual funds for long-term. Having better anticipated returns would also discourage those foreign retail investors from selling the funds, indeed, would motivate them to contribute more into the funds. The findings would be able to guide the Mutual Fund companies in managing and promoting foreign investors and enhancing the mutual funds performances.